Experimental Study on Undrained Shear Properties of Saline Soil under Freeze-Thaw Cycles - Shukai Cheng; Qing Wang; Jiaqi Wang; Yan Han (Geofluids)
The freeze-thaw cycle is an important external factor affecting the hydromechanical characteristics of saline soil in cold regions. Due to the presence of water and salt, it has a greater impact on stability. The construction of various projects, such as ditch fills and road subgrades, has mostly used disturbed soils. Therefore, this article takes remolded saline soil in Qian’an, Jilin Province, China, as the research object to evaluate the action of freeze-thaw cycles on the critical state line, effective stress path, pore water pressure-strain relationship, stress-strain relationship, shear strength index, and other mechanical properties via a freeze-thaw cycle test and a consolidated undrained triaxial shear test (CU). The experimental results show that regardless of whether the soil specimen undergoes a freeze-thaw cycle, its stress-strain relationship shows characteristics of strain hardening, while, as the number of freeze-thaw cycles increases, the shear strength gradually decreases. As both the confining pressure and number of freeze-thaw cycles increase, the pore water pressure increases, as does the pore water pressure coefficient in shear failure. Under the action of freeze-thaw cycles, on the p′−q plane of the stress space, the effective stress path gradually moves to the lower left side. Both the effective stress path and the pore water pressure characteristics indicate that the degree of consolidation of the soil specimens continuously decreases as the number of freeze-thaw cycles increases. The position of the critical state line gradually lowers, and the critical state stress ratio decreases. The effective stress strength index can more accurately reflect the comprehensive influence of freeze-thaw cycles and confining pressure on the mechanical characteristics of soils than the total stress strength index. Logistic functions can be used to fit and predict the degradation law of the internal friction angle and cohesion.